(untitled) (Prithvi Academic Journal, 2019)
The main objective of this paper is to assess the level of patient satisfaction, to assess barriers faced by users of social health insurance during receiving treatment in the hospital, and to find out the relationship of participants’ satisfaction with their selected demographic variables. This paper is a cross-sectional descriptive study and covers 354 samples that were selected by systematic sampling technique. The modified version of Assessment of Patients Satisfaction Scale (SAPS) consisting of seven structured items is used to collect the data through the face to face interview. The results of the study indicated that 158 (44.6%) participants are between the age group of 40-59 years and the majority of them i.e. 232 (65.5%) are females. Out of 354, most of the participants 292 (82.5%) are enrolled in the social health insurance scheme for more than 6 months. The study findings indicated that more than half 186 (52.5%) participants are satisfied, followed by 152 (42.9%) are dissatisfied, and 16(4.5%) of participants are very dissatisfied with the treatment service under the social health insurance respectively. The most common barriers faced by the participants while utilizing the health insurance services are unavailability of necessary drugs, long waiting times, limited opening hours, and complex billing system for insurance patients. Hence, the service availability time should be extended and availability of health personnel, medicines as well as other services should be improved that can increase satisfaction among users of health insurance.